2020
DOI: 10.3390/app10082668
|View full text |Cite
|
Sign up to set email alerts
|

Uncaria tomentosa (Willd. ex Schult.) DC.: A Review on Chemical Constituents and Biological Activities

Abstract: Uncaria tomentosa (Willd. ex Schult.) DC. (Family: Rubiaceae), commonly known as cat’s claw, is a tropical medicinal vine originating at the Amazon rainforest and other areas of South and Central America. It has been traditionally used to treat asthma, abscesses, fever, urinary tract infections, viral infections, and wounds and found to be effective as an immune system rejuvenator, antioxidant, antimicrobial, and anti-inflammatory agent. U. tomentosa is rich in many phytoconstituents such as oxindole and indol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 60 publications
0
43
0
6
Order By: Relevance
“…This study was performed to identify whether certain components of U. tomentosa extracts have potential therapeutic effects against COVID-19. To this purpose, a database of 26 compounds that have shown prevalence on the herbal therapeutic activity has been generated ( Figure 1) (Aquino et al, 1990(Aquino et al, , 1997Batiha et al, 2020;Keplinger et al, 1998;Kitajima et al, 2000;Lima-Junior et al, 2013;Lock et al, 2016;Montoro et al, 2004;Navarro et al, 2019Pavei et al, 2012;Peñaloza et al, 2015;Snow et al, 2019;Vera-Reyes et al, 2015). Our initial hypothesis is that cat's claw should contain molecules with highest therapeutic profiles against SARS-CoV-2, by disrupting SARS-CoV-2/ACE-2 association or by inhibiting SARS-CoV-2 spike protein.…”
Section: Database Of U Tomentosa Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed to identify whether certain components of U. tomentosa extracts have potential therapeutic effects against COVID-19. To this purpose, a database of 26 compounds that have shown prevalence on the herbal therapeutic activity has been generated ( Figure 1) (Aquino et al, 1990(Aquino et al, , 1997Batiha et al, 2020;Keplinger et al, 1998;Kitajima et al, 2000;Lima-Junior et al, 2013;Lock et al, 2016;Montoro et al, 2004;Navarro et al, 2019Pavei et al, 2012;Peñaloza et al, 2015;Snow et al, 2019;Vera-Reyes et al, 2015). Our initial hypothesis is that cat's claw should contain molecules with highest therapeutic profiles against SARS-CoV-2, by disrupting SARS-CoV-2/ACE-2 association or by inhibiting SARS-CoV-2 spike protein.…”
Section: Database Of U Tomentosa Bioactive Compoundsmentioning
confidence: 99%
“…Bioactive constituents of U. tomentosa extracts include proanthocyanidins [proanthocyanidin B2 (the main component), proanthocyanidin B4, proanthocyanidin C1, an epicatechin trimer, epiafzelechin-4b!8-epicatechin and an epicatechin tetramer] (Batiha et al, 2020;Navarro-Hoyos et al, 2017), oxindole alkaloids (isopteropodine, pteropodine, rhynchophylline, mytraphylline, speciophylline, uncarine F and uncarine E), indole alkaloidal glucosides (cadambine, 3dihydrocadambine and 3-isodihydrocadambine) (Batiha et al, 2020;Kura s et al, 2009;Laus et al, 1997;Lima-Junior et al, 2013;Lock et al, 2016;Navarro et al, 2019Snow et al, 2019), quinovic acid glycosides (Pavei et al, 2012), tannins (Ostrakhovich et al, 1997), polyphenols, catechins, beta sitosterol (Aquino et al, 1997;Navarro et al, 2019) and proteins (Lenzi et al, 2013), which individually or synergistically contribute to their therapeutic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The results from this study demonstrated that exposure to FA led to a significant decline in antioxidant markers [ 52 ], with a concomitant increase in liver transaminases, lipid profile as well as inflammatory markers [ 53 ]. Additionally, G. lucidum possesses protective roles as it has the ability to restore antioxidant, lipid profile and anti-inflammatory statuses.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants have been used for various therapeutic purposes. U. tomentosa has been traditionally used to treat asthma, abscesses, fever, urinary tract infections, viral infections, and wounds (Batiha et al, 2020). It also has been used to treating diabetes, cancer, intestinal affections inflammation, cancer, menstrual disorders (de Paula et al, 2015;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…U. tomentosa has several pharmacological activities such as antitumor, anticancer, antioxidant, anti-neoplastic, antiinflammation, antimicrobial, antiprotozoal, and antiviral activities (Batiha et al, 2020). Cytotoxic activity of ethanol extract from hooks U. tomentosa from West Kalimantan is not known.…”
Section: Introductionmentioning
confidence: 99%